Immigration, Discrimination, and Trust: A Simply Complex Relationship - Wilkes, Rima; Wu, Cary (Frontiers in Sociology, 2019)
Trust is integral to the process of immigrant integration. While previous research has considered whether discrimination has an effect on trust, no study has considered the specific extent to which immigrants experience more discrimination than the native-born and how this might matter for immigrant-native gaps in trust. To address this issue we provide the first study to use a formal mediation approach to studying the immigration, discrimination, and trust relationship. Drawing on the 2013 Canadian General Social Survey data (N=27,695) we analyze differences in three kinds of trust (generalized, specific others and political), and the role of discrimination, between Canadian-born whites, Canadian-born people of colour, foreign-born whites, foreign-born people of colour, and Indigenous people. We find that discrimination has a greater impact on social rather than political relationships. Immigrants have lower social trust in general and in others because of race-based discrimination rather than because they are immigrants per se.